Patofiziologija akutnih koronarnih sindromov - Starc, Radovan (Medicinski razgledi, 2002)
The authors discuss the fundamentals of the pathological and pathophysiological processes in coronary arteries that lead to acute coronary syndrome.
Keywords: Angina nestabilna; Myocardial infarction; Physiopathology; Koronarna arterioskleroza; Miokardni infarkt; Angina, unstable; Death, sudden, cardiac; Smrt nenadna, srčna; Angioplastika transluminalna, perkutana, koronarna; Coronary arteriosclerosis; cardiovascular disease; Angioplasty, transluminal, percutaneous coronary; kardiovaskularne bolezni; ateroskleroza; angina pectoris